Phytochemicals Screening, Proximate composition and Antioxidants Analysis of Italian Citrus paradisi Fruits - Bandi, Ibrahim Iklimah; Ibrahim, Abubakar; Shehu, Ibrahim; Gobir, Adiya Zainab Sarkin; Bature, Buhari Hafsat; Rara, Shehu Samira (Journal of Tropical Pharmacy and Chemistry, 2024)
Citrus paradise is a largely consumed fruit for nutrition and medicinal importance. This study was conducted to evaluate the phytochemicals, proximate, and antioxidants contents of Italian Citrus paradisi fruits. The phytochemicals screening and proximate analysis were performed using the methods of AOAC. Antioxidants contents and capacities of the extract were determined by DPPH and FRAP Assay. The grapefruits aqueous extract revealed the presence of various phytochemicals and contains significant (p < 0.05) amount of carbohydrates (89.36 %), moisture (74.80 %), lipids (4.56 %), protein (3.36 %), crude fiber (2.36 %), and ash content (0.83 %). The extract exhibited significant (p < 0.05) increase in DPPH percentage inhibition of free radical scavenging activity and FRAP properties comparable to that of the standard, ascorbic acid. The grapefruits extract contains various phytochemicals, proximate nutrients, and exhibited free radical scavenging activity. The grapefruits have nutritional status, antioxidant properties, and medicinal importance.